Testing Social Enterprise Models Across the World: Evidence From the "International Comparative Social Enterprise Models (ICSEM) Project". (April 2021) - Defourny, Jacques; Nyssens, Marthe; Brolis, Olivier
In response to the large number of definitions of social enterprise (SE), various works have sought to cope with such diversity through SE typologies. Many of them are however country-specific and only very few of them are built upon solid theoretical foundations. To overcome these weaknesses, Defourny and Nyssens had put forward, in a previous article, some fundamentals for an international typology, including four SE models. The objective of the present article is to test the existence of these models on the basis of a data set covering 721 SEs and resulting from a survey carried out in 43 countries. More precisely, the statistical exploitation of the data set combined multiple factorial analysis with hierarchical cluster analysis. It appears that the existence of three of the four SE models—namely the social-business model, the social-cooperative model and the entrepreneurial nonprofit model—is strongly supported by the empirical analysis in almost all surveyed countries.